The urgent need for integrated science to fight COVID-19 pandemic and beyond - Moradian, Negar; Ochs, Hans D.; Sedikies, Constantine; Hamblin, Michael R.; Camargo, Carlos A.; Martínez, J. Alfredo; Biamonte, Jacob D.; Abdollahi, Mohammad; Torres, Pedro J.; Nieto, Juan J.; Ogino, Shuji; Seymour, John F.; et al. (Springer, 2020)
The COVID-19 pandemic has become the leading societal concern. The pandemic has shown that the public health concern is not only a medical problem, but also affects society as a whole; so, it has also become the leading scientific concern. We discuss in this treatise the importance of bringing the world’s scientists together to find effective solutions for controlling the pandemic. By applying novel research frameworks, interdisciplinary collaboration promises to manage the pandemic’s consequences and prevent recurrences of similar pandemics.